(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study highlights the growing need for student financial competence amid rapid financial technology development and increasingly complex income management. It examines how financial literacy, financial technology, and income levels influence the financial behavior of students at the Satya Dharma College of Economics. Using a quantitative approach with SEM-PLS, the study involved 83 respondents selected from 498 active students through stratified random sampling and analyzed using SmartPLS. The findings reveal that all three variables—financial literacy, financial technology, and income—positively and significantly affect financial behavior. An R-square value of 0.990 shows that these variables explain 99% of the variation in financial behavior. The results underscore the need to strengthen financial literacy, promote prudent use of financial technology, and improve income management to foster healthier financial habits. This research supports the development of campus financial education programs and provides insights for policymakers to enhance youth financial literacy.